Citrix XenDesktop cookbook : over 40 engaging recipes that will help you implement a full-featured XenDesktop 7.6 architecture and its main satellite components /: over 40 engaging recipes that will help you implement a full-featured XenDesktop 7.6 architecture and its main satellite components. (2015) - Silvestri, Gaspare A
No abstract available